Myocardial ischemia: a silent epidemic in Type 2 diabetes patients. (March 2011) - Le Feuvre, Claude; Jacqueminet, Sophie; Barthelemy, Olivier
The prevalence of diabetes mellitus is increasing consistantly. Coronary artery disease (CAD) is the main cause of death; however, silent myocardial ischemia (SMI) is more frequent in diabetic patients. Early CAD diagnosis provided by SMI screening could lead to decreased cardiovascular complications and mortality. Current guidelines recommend screening for SMI in asymptomatic diabetic patients selected on a basis of high cardiovascular risk, followed by coronary angiogram in case of a positive stress test. However, the benefit of systematic SMI screening has not been demonstrated in diabetic patients with optimal treatment of risk factors. The benefit of revascularization in diabetic patients with SMI seems to be restricted to patients with severe CAD. Prospective studies are required to identify diabetic patients who may potentially benefit from SMI screening. These patients should have a high prevalence of severe CAD and potential benefit of revascularization, such as patients with renal failure, left ventricular dysfunction and peripheral or carotid occlusive arterial disease.